Effects of Allopurinol Dose Escalation on Bone Erosion and Urate Volume in Gout: A Dual‐Energy Computed Tomography Imaging Study Within a Randomized, Controlled Trial. Issue 10 (12th August 2019) - Dalbeth, Nicola; Billington, Karen; Doyle, Anthony; Frampton, Christopher; Tan, Paul; Aati, Opetaia; Allan, Jordyn; Drake, Jill; Horne, Anne; Stamp, Lisa K.
Abstract : Objective: To examine whether allopurinol dose escalation to achieve serum urate (SU) target can influence bone erosion or monosodium urate (MSU) crystal deposition, as measured by dual‐energy computed tomography (DECT) in patients with gout. Methods: We conducted an imaging study of a 2‐year randomized clinical trial that compared immediate allopurinol dose escalation to SU target with conventional dosing for 1 year followed by dose escalation to target, in gout patients who were receiving allopurinol and who had an SU level of ≥0.36 mmoles/liter. DECT scans of feet and radiographs of hands and feet were obtained at baseline, year 1, and year 2 visits. DECT scans were scored for bone erosion and urate volume. Results: Paired imaging data were available for 87 patients (42 in the dose‐escalation group and 45 in the control group). At year 2, the progression in the CT erosion score was higher in the control group than in the dose‐escalation group (+7.8% versus +1.4%; P = 0.015). Changes in plain radiography erosion or narrowing scores did not differ between groups. Reductions in DECT urate volume were observed in both groups. At year 2, patients in the control group who had an SU level of <0.36 mmoles/liter and patients in the dose‐escalation group had reduced DECT urate volume (−27.6 to −28.3%), whereas reduction in DECT urate volume was not observed in control group patients with an SU level of ≥0.36 mmoles/liter (+1.5%) ( P = 0.023). Conclusion: These findings provide evidence that long‐term urate‐lowering therapy using a treat‐to‐SU‐target strategy can influence structural damage and reduce urate crystal deposition in gout.